2018
DOI: 10.1186/s12904-018-0341-1
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of socioeconomic status with place of death: a qualitative analysis of physician experiences

Abstract: BackgroundHome is a preferred place of death for many people; however, access to a home death may not be equitable. The impact of socioeconomic status on one’s ability to die at home has been documented, yet there remains little literature exploring mechanisms that contribute to this disparity. By exploring the experiences and insights of physicians who provide end-of-life care in the home, this study aims to identify the factors perceived to influence patients’ likelihood of home death and describe the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 57 publications
(67 reference statements)
5
12
0
Order By: Relevance
“…The suggestion that availability of social support is the main socioeconomic factor determining place of death has been recognised elsewhere. [37][38][39] The evidence in this review supports the wider literature that suggests preferred place of death is usually, but not always, at home. However, within this broad preference, this study has also shown support for work by Gomes 40 that found preference for home care substantially decreased in the final few weeks of life, supporting Pollock's 41 view that home may not always be the best place to die.…”
Section: What This Study Addssupporting
confidence: 79%
“…The suggestion that availability of social support is the main socioeconomic factor determining place of death has been recognised elsewhere. [37][38][39] The evidence in this review supports the wider literature that suggests preferred place of death is usually, but not always, at home. However, within this broad preference, this study has also shown support for work by Gomes 40 that found preference for home care substantially decreased in the final few weeks of life, supporting Pollock's 41 view that home may not always be the best place to die.…”
Section: What This Study Addssupporting
confidence: 79%
“…The correlation found between dying at home and socioeconomic status has been previously reported in other countries [8]. The mechanisms whereby socioeconomic status affects one's ability to die at home may involve various factors: the ability to provide adequate care at home, adequate access to care services, care-related costs, control over monetary resources, the ability to secure local support, and personal preferences [9]. Socioeconomic status may, however, in uence or be in uenced by other dominant variables.…”
Section: Discussionsupporting
confidence: 66%
“…The association found between dying at home and socioeconomic status has been previously reported in other countries [8]. The mechanisms whereby socioeconomic status affects one's ability to die at home may involve various factors: whether a person lives alone, the ability to provide adequate care at home, adequate access to care services, care-related costs, control over monetary resources, the ability to secure local support, and personal preferences [9]. Socioeconomic status may, however, in uence or be in uenced by other dominant variables.…”
Section: Discussionsupporting
confidence: 56%